Performance and Analysis of Optical Fiber Communication System Using MZI Switching - Teotia, Pradeep Kumar (My University, 2009)
First a simple all-optical logic device, called Mach Zhender Inferometer is composed by using a Semiconductor Optical Amplifier (SOA) and an optical coupler. This device is used for generating the logical functions (AND, XOR) and a multiplexer and an Encoder is obtained using this device in Optical Tree Architecture. The simulation of Encoder and Multiplexer is done at a rate of 10 Gbit/s and both are simulated for different input logical combinations. Simulations indicate that the device is suitable to operate at much higher bit rate and also for different logical entities. A fiber communication system is employed using Giga Ethernet Passive Optical Network (GE-PON) architecture. In this architecture an optical fiber is employed directly from a central office to the home. A 1:8 splitter is used as a PON element which establishes communication between a central office to different users. In this chapter GE-PON architecture has investigated for different lengths from a central office to the PON in the terms of BER. For 10 Gbit/s system the plots between the BER and transmission distance is plotted and it is seen that as the distance increases beyond the 15 Km the BER is increasedvery sharply. Results in the form of Voice and Data spectrum for different users of FTTHwith GE-PON architecture are shown. Many lower-speed data streams can be multiplexed into one high-speed stream by means ofOptical time division multiplexing (OTDM), such that each input channel transmits its datain an assigned time slot. The assignment is performed by a fast multiplexer switch (mux).The routing of different data streams at the end of the TDM link is performed by ademultiplexer switch (demux) and this demultiplexer is employed using MZI switch as itconsists a semiconductor optical amplifier (SOA) and a optical coupler. In this chapter fourchannel OTDM is simulated at 40 Gbit/s and further it is investigated the impact of the signalpower, pulse width and control signal power on BER.
M.E. (
Keywords: FTTH; TOAD; MZI; OTDM